PELATIHAN DASAR JARINGAN KOMPUTER UNTUK SISWA SMK TEKNIK KOMPUTER JARINGAN PADA LKP PELITA MEDIA - Maha Putra, Guntur; Junaidi; Bela, Bela Astuti (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2025)
Abstract: This activity aims to enhance students’ competence in understanding the basic concepts of computer networks as well as mastering the skills of network installation and configuration. The main problems faced by the students include limited learning resources, lack of practice-based training, and minimal access to adequate networking equipment, resulting in low readiness to enter the industrial workforce. This program provides a solution through a learning approach that combines theoretical instruction, hands-on practice, and case studies aligned with industry demands. The activities include preparation of training materials, implementation of training across four main sessions, and a final evaluation through both theoretical and practical examinations. The expected outcomes of this program include improved student competencies, the development of training modules, certificates of participation, and comprehensive documentation for evaluation and publication purposes. Through this program, it is expected that TKJ vocational students will be better prepared to enter the workforce and possess skills that are relevant to current advancements in computer networking technology. Keywords: evaluation; industry; network; competence; training; Abstrak: Kegiatan ini bertujuan untuk meningkatkan kompetensi siswa dalam memahami konsep dasar jaringan komputer serta menguasai keterampilan instalasi dan konfigurasi jaringan. Permasalahan utama yang dihadapi siswa adalah keterbatasan sumber belajar, kurangnya pelatihan berbasis praktik, dan minimnya akses terhadap perangkat jaringan yang memadai, yang mengakibatkan rendahnya kesiapan mereka dalam memasuki dunia industri. Kegiatan ini menawarkan solusi melalui pendekatan pembelajaran berbasis teori, praktik langsung, dan studi kasus yang relevan dengan kebutuhan industri. Kegiatan ini mencakup persiapan materi, pelaksanaan pelatihan dalam empat sesi utama, serta evaluasi akhir melalui ujian teori dan praktik. Luaran yang diharapkan dari program ini meliputi peningkatan kompetensi siswa, pembuatan modul pelatihan, sertifikat serta dokumentasi kegiatan sebagai bahan evaluasi dan publikasi. Dengan terlaksananya program ini, diharapkan siswa SMK TKJ lebih siap menghadapi dunia kerja serta memiliki keterampilan yang relevan dengan perkembangan teknologi jaringan komputer. Kata kunci: evaluasi; industri; jaringan; kompetensi; pelatihan